Contribuições da Teoria da Reprodução Social (TRS) à análise do trabalho de assistentes sociais - Blanco, Larissa Moretti (2023)
This dissertation aims to look at the contributions of Social Reproduction Theory (SRT), especially its contemporary elaborations, to the analysis of the work of social workers. The perspective in question arose in the wake of the feminist-Marxist debates on domestic work in the 1970s and is based on the critique of political economy, i.e. Karl Marx's labor theory of value, in order to analyze the free labor performed by women in the private sphere of the home, in the production and reproduction of the labor force, the special commodity of the capitalist mode of production. Reproductive work, materialized by multiple processes that guarantee the birth and survival of workers from a physical and emotional point of view, can take place in the family, the main instance in which female figures carry out care work; in the market, through the commodification of basic needs (such as access to health, for example, which is now mediated by the acquisition of medical insurance); and also by the state and its public institutions responsible for implementing public social policies and services - the major sphere in which social workers carry out their work processes. It is in this context that, since the genesis of the profession, social workers have focused on meeting the survival needs of the working class - needs that always fall short of the real demands of this class, insofar as profit subordinates life in the capitalist logic, even though capitalism cannot do without the reproduction of its special commodity: labor power. Starting from a critical interpretation of Social Work as work and its historical insertion in the reproductive sphere, responsible for materializing a way of reproducing the life of the working class in line with capitalist interests, mostly through the state at its service, we seek to discuss what theoretical-methodological and ethical-political advances can emerge in the analysis of professional work in a situation as challenging as the current one, precisely from the centrality of the category reproduction of the workforce, proposed by the unitary perspective of the Social Reproduction Theory (SRT). Furthermore, given that the SRT seeks to understand the relations of oppression as intrinsic to the functioning of capitalism, and not as independent systems, through the centrality of the Marxian category of social totality, this dissertation also seeks to understand and expose the contributions of this perspective to the debates on gender relations and ethnic-racial relations – and, consequently, to the strengthening of the ethical-political project – given the importance that these discussions have achieved within the profession in recent years, even if they are not always ontologically linked to the anti-capitalist discussion. In this sense, one of the conclusions of our research pointed out that qualified adherence to the ethical-political project depends on it being in line with the real demands of the working class and, on this point, Social Work echoes the SRT effort to consider the subjectivities and unequal experiences of the working class, by focusing on the multiple reproductive processes that inhumanely forge it